Peningkatan Kinerja Karyawan dengan Gaya Kepemimpinan Transformasional dan Budaya Organisasi - Dewantari, Ni Gusti Ayu Mas; Wijaya, Putu Yudi; Puja, I Made Suasti (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
The potential of the company in achieving its goals is very dependent on the results shown by employees while carrying out their duties. This is an important foundation in carrying out all activities that will affect the success of the company. This study has a goal, namely to be able to determine the increase in employee performance with a transformational leadership style and organizational culture. Rimbun Canggu Hotel & Villas in Badung is the research location. The entire population totaled 38 employees so that all of them were used as samples to be examined. Analysis of the data collected will use multiple linear regression methods. The results show that there is a positive and significant increase in performance with transformational leadership and organizational culture. The advice given is to continue to improve and develop a transformational leadership style and organizational culture to maximize performance.